El Cómic En La Clase De Ele: Las Actitudes De Los Estudiantes De Profesorado Y Algunas Repercusiones - Laurent-Fidèle Sossouvi (European Scientific Journal, ESJ, 2017)
Many researchers have considered comics as an excellent educational resource, pointing out to its advantages and its great educational potential. As a result, few authors have investigated the attitudes of students towards comics and they are rarely used as a teaching material in Benin in the learning of foreign languages. In this study, we aim to examine the attitudes of Beninese students of Spanish as a Foreign Language towards comic, as well as offer a reflection on some of the possibilities that can bring this teaching resource. In doing this, we analyze data from 25 participants which was obtained from a questionnaire, interviews, and tasks around the comic. Conclusions show that: (a) most participants showed a positive attitude towards comics and are highly motivated; (b) the use of comics contributed to improving their linguistic and intercultural communicative competences, as well as revitalized the learning of the target language. Finally, the paper concludes by pointing out the study’s implications and limitations, and offering suggestions for future research opportunities.